Respuesta :
Answer:
x = 11.
Step-by-step explanation:
√(x - 2) + 8 = x
√(x - 2) = x - 8
Square both sides:
x - 2 = (x - 8)^2
x - 2 = x^2 - 16x + 64
x^2 - 17x + 66 = 0
(x - 6)(x - 11) = 0
x = 6, 11.
With this type of question we could have extraneous roots so:
Check these 2 roots:
x = 6:
√(2 - 6) + 8 = √(-4)+8 <----- has no real value so this is not a root,
x = 11:
√(11-2) + 8 = 11 < ----Checks out.
Answer:
- x = {6, 11}
Step-by-step explanation:
- [tex]\sqrt{x-2} + 8=x[/tex]
- [tex]\sqrt{x-2} = x - 8[/tex]
- x - 2 = (x - 8)²
- x² - 16x + 64 = x - 2
- x² - 17x + 66 = 0
- x = (17 ± [tex]\sqrt{17^2- 4*66}[/tex]) / 2
- x = (17 ± 5)/2
- x = 11
- x = 6